Ảnh hưởng của năng lực tâm lý đến cam kết làm việc và kết quả công việc của nhân viên: Trường hợp doanh nghiệp điện-điện tử trong các Khu công nghiệp tại TP. Hồ Chí Minh - Phan Quoc, Tan; Bui Thi , Thanh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This research examines the relationship between psychological capital, work engagement, and performance of employees. Surveyed data was collected from 501 employees working at electrical and electronic enterprises in the Industrial zones Ho Chi Minh City. The result of structural equation modeling (SEM) showed that psychological capital has a strong positive impact on work engagement and performance of employees; work engagement has a lower positive impact on performance. Based on the findings, some implications are drawn to help that the managers of electrical and electronicenterprises improve human resource policies to enhance psychological capital well-being, thereby increasing employee engagement and performance.